2019
DOI: 10.33263/briac101.908913
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of magnetic nanoparticles of cobalt ferrite coated with silica

Abstract: There are several methods available for magnetic nanoparticles (MNP) synthesis, and in this study the coprecipitation method is employed. The cobalt ferrites (CF) were prepared using aqueous solutions of Co2+ and Fe3+ chloride with a stoichiometry proportion of Co:Fe = 1:2. Thus, the aging temperatures were 27, 27/98, 60, 80 and 98 ºC, during which the precipitation occurred at 27 °C and the aging one at 98 °C for the FC27/98 sample. As a result, the study showed that a single crystal phase material was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recent reports suggested that bi-magnetic core-shell nanocrystals can improve the energy production of the magnetic nanoparticles beyond the superparamagnetic limit for applications, particularly in magnetic storage [11]. The magnetic properties of core-shell structures are usually determined by several parameters such as the size, order (soft-hard or hard-soft), and geometric shape of the core and shell [12][13][14]. Furthermore, the magnetic properties are affected by differences in magnetic parameters between the core and shell materials, as well as the presence of dipolar and exchange-coupled interactions that affect spin reversal processes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggested that bi-magnetic core-shell nanocrystals can improve the energy production of the magnetic nanoparticles beyond the superparamagnetic limit for applications, particularly in magnetic storage [11]. The magnetic properties of core-shell structures are usually determined by several parameters such as the size, order (soft-hard or hard-soft), and geometric shape of the core and shell [12][13][14]. Furthermore, the magnetic properties are affected by differences in magnetic parameters between the core and shell materials, as well as the presence of dipolar and exchange-coupled interactions that affect spin reversal processes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 The influence of aging temperature on the synthesis of nanocomposites of ferrit with silica by the Stöber method was studied. Queiroz et al [104] investigated vario aging temperatures-98, 80, 60, 27/98, and 27 °C-for the synthesis of silica-coated cob ferrite. Aging temperatures of 98 and 27/98 °C give the best suited conditions for prepa ing the single phase of cobalt ferrite.…”
Section: Stöber Methodsmentioning
confidence: 99%
“…Nevertheless, the properties of Fe 3 O 4 nanoparticles depend on their preparation method, and many synthesis techniques have been employed to obtain optimal characteristics for different end purposes. Methods, such as co-precipitation, thermal decomposition, sol-gel, microemulsion, hydrothermal, sonochemical, electrochemical, and biological synthesis have been shown to successfully produce Fe 3 O 4 nanostructures [24,28,[32][33][34]. One of the simplest and most widely used chemical methods for obtaining nanosized Fe 3 O 4 is co-precipitation [35][36][37], particularly due to its simplicity, high yields, and potential for reduced time-consuming, making it easily scalable in industrial applications [37].…”
Section: Introductionmentioning
confidence: 99%